1997
DOI: 10.2307/2952169
|View full text |Cite
|
Sign up to set email alerts
|

The “Veepstakes”: Strategic Choice in Presidential Running Mate Selection

Abstract: We examine the presidential nominees' choice of running mate in each election since 1940, when Franklin Roosevelt established a precedent by naming his own. To analyze the 22 choices made from the pool of 127 serious possibilities, we employ a discrete choice model. We find that the presidential nominee's choice is explained primarily by the size of the prospective vice president's state, by whether the running mate finalist was a rival for the nomination, and by the balance in age for the ticket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 8 publications
1
66
2
1
Order By: Relevance
“…In many ways, Sarah Palin was a particularly enigmatic and counterprototypical vicepresidential candidate. She was a relatively unknown political figure at the national level prior to being chosen as McCain's running mate and later the Republican nominee for Vice President, whereas most candidates for Vice President have had a more prominent national image when they were selected (Sigelman and Wahlbeck 1997). Palin is a conservative Republican, whereas most women who run for political office are more liberal Democrats (Dolan 2004).…”
Section: Why So Much Focus On Sarah Palin's Image?mentioning
confidence: 98%
“…In many ways, Sarah Palin was a particularly enigmatic and counterprototypical vicepresidential candidate. She was a relatively unknown political figure at the national level prior to being chosen as McCain's running mate and later the Republican nominee for Vice President, whereas most candidates for Vice President have had a more prominent national image when they were selected (Sigelman and Wahlbeck 1997). Palin is a conservative Republican, whereas most women who run for political office are more liberal Democrats (Dolan 2004).…”
Section: Why So Much Focus On Sarah Palin's Image?mentioning
confidence: 98%
“…2. Note that studies on vice-presidential selection have identified several variables unrelated to geographic balancing that influence this process of selection (see Sigelman & Wahlbeck, 1997). 3.…”
Section: Notesmentioning
confidence: 99%
“…When choosing a running mate, presidential nominees must balance two potentially competing goals: maximizing their chances of actually being elected president and selecting a vice president who is capable of sharing the burdens of government and, if necessary, succeeding to the presidency. Because the latter is meaningless without the former, the academic and popular consensus is that electoral motivations drive the choice of a running mate (Goldstein 1982; Natoli 1985; Polsby and Wildavsky 1991; Sigelman and Wahlbeck 1997). Generally, the conventional wisdom is that presidential candidates seek to balance their ticket by choosing a running mate who contributes key qualities that the presidential nominee lacks.…”
Section: The Changing Incentives Of Vice Presidential Selectionmentioning
confidence: 99%